Mother's Milk Messaging™: trial evaluation of app and texting for breastfeeding support - Maya Bunik; Andrea Jimenez-Zambrano; Michael Solano; Brenda L. Beaty; Elizabeth Juarez-Colunga; Xuhong Zhang; Susan L. Moore; Sheana Bull; Jenn A. Leiferman (BMC, 2022)
Abstract Background New mothers experience BF challenges but have limited evidence-based technology-enabled support. Objectives 1) Determine if using the Mother's Milk Messaging™ app improved aspects of breastfeeding and breastfeeding rates and 2) Describe engagement as well as themes from the qualitative feedback on the app. Method Randomized Controlled Trial National sample of primiparous, singleton mothers recruited online and then randomized using stratification by language into three arms: 1) BF text messages plus app; 2) BF text messages, app and physician-moderated private Facebook (FB) group; 3) Attention control group who received injury prevention texts. Exclusive breastfeeding rates as primary outcome and knowledge/attitude, confidence, and social support as secondary outcomes. We determined engagement through analysis of app usage metrics. We conducted and content-coded interviews with participants to learn more about app usage and BF experience. Due to the nature of the intervention participants could not be blinded. Results There were a total of 346 participants in the trial, with 227 in the Intervention (n = 154 group 1 and n = 156 group 2) and 119 in the control group. Because of minimal Facebook activity, the two intervention groups 1 and 2 were combined. There were no differences in breastfeeding exclusivity and duration. (NS). Women in the intervention arm reported significantly higher confidence with breastfeeding and perceived social support to the control group (p < .05). Greater than 80% registered the app and those that engaged with the app had higher scores with time. Mothers appreciated receiving text messages and videos with reliable information. No harm was reported in this study. Conclusion MMM increased confidence with breastfeeding and with gathering social supports. Exclusively BF was high in all participants. Mothers perceived it as useful and dependable especially the texting.